İş Güvencesinin Muhtemel Ekonomik ve Sosyal Etkileri - (:unkn) unknown (My University, 2003)
0

One of the most important subject and purpose of the modern labour law is to arrange the relationship between employee and employer. One of the legal means, which are regulating labour relations, in labour law, is job security. Job security is the most important tool, that provides labours continuity and labour peace and it has a lot of dimension. In other hands, job security has economic and social dimension in addition to its legal dimension. In these study we take up narrow and extensive meaning of job security and relations between job security and freedom of agreement that is the main concept of law of debts. And then, we explain economic and social influences of job security in the context of the effect of job security to national and international competition relations, to employment, choosing staff and technology, productivity, foreign capital and income distribution.